Mixed-method analysis of published national one health strategic plans - Caroline S. Wilhelm; Amélie Desvars-Larrive; Chris Walzer (iScience)
Summary: In this article, we used a mixed analytical framework to assess existing National One Health Strategic Plans (NOHSPs) and evaluate their alignment with recognized One Health principles. Eight NOHSPs were examined following a qualitative content analysis and key One Health characteristics were identified. Quantitative text analysis was performed to assess unigrams and bigrams frequencies across the NOHSPs. Network analysis was conducted to explore the conceptual relationships surrounding the term ''health'' in each document. Results revealed varying levels of alignment with contemporary One Health principles. Notably, while all plans recognized the importance of cross-sectoral collaboration and environmental health, specific actions were inconsistently anticipated. Additionally, disparities in addressing issues such as climate change, anthropogenic drivers, and non-communicable diseases were evident. Overall, the study offers insights into the strengths and gaps in existing NOHSPs. Moreover, it provides a flexible analytical framework to guide stakeholders in developing and evaluating future One Health initiatives.